2010
DOI: 10.5021/ad.2010.22.2.156
|View full text |Cite
|
Sign up to set email alerts
|

An Open, Randomized, Comparative Clinical and Histological Study of Imiquimod 5% Cream Versus 10% Potassium Hydroxide Solution in the Treatment of Molluscum Contagiosum

Abstract: Background: Although molluscum contagiosum (MC) resolves spontaneously, there are several reasons to treat this dermatological disorder. Objective: To evaluate the safety and efficacy of 5% imiquimod cream versus 10% potassium hydroxide (KOH) solution in treating MC, and to propose the mechanism of cure by observing the histological findings. Methods: Imiquimod or KOH were applied by the patient or a parent 3 days per week until all lesions cleared. The number of MC lesions was counted and side effects were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 9 publications
0
27
0
3
Order By: Relevance
“…The results of this study suggested that both treatments were equally effective (12,13). The concentration of KOH was correlated with side effects.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The results of this study suggested that both treatments were equally effective (12,13). The concentration of KOH was correlated with side effects.…”
Section: Discussionmentioning
confidence: 70%
“…Therapy with KOH was found to be effective and safe in the treatment of MC in children (8)(9)(10)(11)(12)(13). The combination of salicylic acid and lactic acid (SAL + LAC) which demonstrates keratolytic effect is also an efficient alternative treatment in children with MC (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of KOH 10% with imiquimod 5% cream were compared and both agents were equally effective (1,8), but KOH had a faster onset of action (8).…”
Section: Resultsmentioning
confidence: 99%
“…Molluscum contagiosum (MC) is a self-limited condition but due to its unattractive nature and possibility for transmission, it is recommended that it be treated (1,2). The treatment options are based on destructive or immune modulating modalities (1).…”
Section: Introductionmentioning
confidence: 99%
“…Also, 5% potassium hydroxide has been compared with 0.05% tretinoin cream;13 and 10% potassium hydroxide with salicylic acid plus lactic acid;14 cryotherapy;15 and imiquimod;16 all the trials were open-label with small numbers of patients (26-50 participants). No one treatment showed a clear benefit.…”
Section: About Potassium Hydroxidementioning
confidence: 99%